Pesan Kreatif Iklan Televisi Dalam Bulan Ramadan: Analisis Semiotika Iklan Bahagianya adalah Bahagiaku - Andrianto, Novan (Faculty of Communications Science, Dr. Soetomo University, 2018)
The commercial advertising is one the most famous and the most discussed promotion tool because of its scope. One of the products using Television Commercial, as the promotion tool in Ramadan, is Ramayana Department Store. Before and During the Ramadan, most Moslems have their activities in Ramadan with themselves, their society, their colleagues and their beloved families. In Ramayana Ramadan Commercial